2009
DOI: 10.1099/vir.0.009092-0
|View full text |Cite
|
Sign up to set email alerts
|

Acidic residues in the membrane-proximal stalk region of vaccinia virus protein B5 are required for glycosaminoglycan-mediated disruption of the extracellular enveloped virus outer membrane

Abstract: The extracellular enveloped virus (EEV) form of vaccinia virus (VACV) is surrounded by two lipid envelopes. This presents a topological problem for virus entry into cells, because a classical fusion event would only release a virion surrounded by a single envelope into the cell. Recently, we described a mechanism in which the EEV outer membrane is disrupted following interaction with glycosaminoglycans (GAGs) on the cell surface and thus allowing fusion of the inner membrane with the plasma membrane and penetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…The L1 staining of EV is likely due to ruptures in the EV membrane that occurred during processing of the samples, which exposed the IMV antigens. EV that lack B5 were reported to have a more stable outer envelope (Roberts et al, 2009). This stability likely accounts for the lack of L1 staining of the EV particles released from cells infected with vB5R-GFP/ΔA33R as they do not contain B5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The L1 staining of EV is likely due to ruptures in the EV membrane that occurred during processing of the samples, which exposed the IMV antigens. EV that lack B5 were reported to have a more stable outer envelope (Roberts et al, 2009). This stability likely accounts for the lack of L1 staining of the EV particles released from cells infected with vB5R-GFP/ΔA33R as they do not contain B5.…”
Section: Resultsmentioning
confidence: 99%
“…B5 has been reported to play a role in the dissolution of the outermost membrane of EEV to allow IMV to enter cells (Roberts et al, 2009). Therefore, the smaller plaque phenotype of vB5R-GFP/ΔA33R suggests two possibilities: less enveloped virions are produced by vB5R-GFP/ΔA33R compared to vΔA33R or enveloped virions produced by vB5R-GFP/ΔA33R are less infectious as they lack B5.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the cytoplasmic tail (25) and a large portion of the extracellular domain of B5 (14) are not required for EV formation, indicating an important role for the transmembrane domain and the coiled-coil structure of B5. In addition, the coiled-coil structure, or stalk, has been reported to be critical for ligand-induced rupture of the outer EEV membrane (34). The fact that A33-HA interacts with ⌬/cc/G/⌬-Strep, a construct that has only the coiled-coil domain of B5 and the transmembrane domain of VSVG, suggests that the coiled-coil domain of B5 is sufficient for interaction with A33 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the possibility that B5 and A33 mediate cooperative target cell binding. A34 and B5 have been shown to be present as a complex on the surface of EEV (27). It has also been reported that in the absence of B5, A34 is present at a reduced level (2).…”
Section: Figmentioning
confidence: 97%